Neonatal sclerosing cholangitis with novel mutations in DCDC2 (doublecortin domain-containing protein 2) in Chinese children - Wei, Xia; Fang, Yuan; Wang, Jian-She; Wang, Yi-Zhen; Zhang, Yuan; Abuduxikuer, Kuerbanjiang; Chen, Lian (Frontiers in Pediatrics, 2023)
Background Neonatal sclerosing cholangitis (NSC) is a rare and severe autosomal recessive inherited liver disease with mutations in DCDC2, commonly requiring liver transplantation (LT) for decompensated biliary cirrhosis in childhood. Methods The information of four Chinese patients with NSC caused by mutations in DCDC2 from Children's Hospital of Fudan University were gathered. The four patients' clinicopathological and molecular features were summarized by clinical data, liver biopsy, immunohistochemical, and molecular genetic analysis. Results All patients presented with jaundice, hepatosplenomegaly, hyperbilirubinemia and bile embolism, and high serum γ-glutamyl transferase activity (GGT). Liver biopsies revealed varying degrees of bile duct hyperplasia, portal-tract inflammation, and/or fibrosis. Whole-exome sequencing (WES) found novel heterozygous variants of c.1024-1G > T /p.? and c.544G > A /p. Gly182Arg in the DCDC2. Conclusion This study expands the genetic spectrum of DCDC2 in NSC.